Induction motor drive based on direct torque controlled used multi-pulse AC-DC rectifier - Rohollah Abdollahi (International Journal of Applied Power Engineering (IJAPE), 2021)
This paper presents the direct torque-controlled induction motor drives (DTCIMDs) based on a retrofit 44-pulse rectifier (44PR). A 22-phase polygon autotransformer (PA) is designed to supply the rectifiers. The above structure improves the power quality standards in the power grid and complies with the requirements of the IEEE-519 standard for different loads. Besides, a power factor close to one is obtained for a wide range of DTCIMD performance. The results show that the total harmonic distortion (THD) of the input current under variable loads for 44PR is less than 3%.